2019
DOI: 10.1186/s13601-019-0292-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe systemic sting reactions in wasp (Vespula spp.) and honeybee (Apis mellifera) venom allergic patients

Abstract: Background Hymenoptera stings are a major cause of anaphylaxis. Various risk factors are discussed in literature. This study aims to investigate potential risk factors for severe sting reactions in wasp (Vespula spp.) and honeybee (Apis mellifera) venom allergic patients and analyses the correlation between diagnostic test results and the severity of the allergic reaction. Methods 480 patients suffering from wasp or honeybee venom al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
3
20
0
2
Order By: Relevance
“…Literature data indicate that in patients with anaphylaxis, the presence of cardiovascular disease has been shown to predispose them to fatalities [ 13 , 19 , 20 , 23 , 37 ], and it is probable that other chronic conditions such as renal and pulmonary problems would do likewise [ 59 ]. Concomitant cardiac conditions were an important predictor of severe anaphylaxis in the analysis of food-elicited reactions [ 35 ] and in patients with anaphylaxis induced by Hymenoptera venom [ 47 , 60 ], which is consistent with findings from our analysis. Recent medical history in elderly patients consisted of significantly more frequent cardiovascular, thyroid, and malignant diseases [ 61 ].…”
Section: Analysis Of Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Literature data indicate that in patients with anaphylaxis, the presence of cardiovascular disease has been shown to predispose them to fatalities [ 13 , 19 , 20 , 23 , 37 ], and it is probable that other chronic conditions such as renal and pulmonary problems would do likewise [ 59 ]. Concomitant cardiac conditions were an important predictor of severe anaphylaxis in the analysis of food-elicited reactions [ 35 ] and in patients with anaphylaxis induced by Hymenoptera venom [ 47 , 60 ], which is consistent with findings from our analysis. Recent medical history in elderly patients consisted of significantly more frequent cardiovascular, thyroid, and malignant diseases [ 61 ].…”
Section: Analysis Of Results and Discussionsupporting
confidence: 89%
“…Current German and European guidelines recommend Venom Immunotherapy (VIT) for all patients with grade II or higher reactions and for patients with a grade 1 reaction if they have any other risk factors or if their quality of life has been negatively impacted [ 43 , 44 , 45 , 46 ]. Other risk factors for severe anaphylaxis triggered by insect sting include male sex, older age, a large number of stings, a short time interval between stings, the location of the sting, the absence of skin symptoms, high baseline serum tryptase levels, as well as cardiovascular comorbidity [ 47 ]. Oropeza et al [ 48 ] also reported other risk factors, such as asthma, rhinitis, atopic dermatitis, urticaria, and/or angioedema.…”
Section: Introductionmentioning
confidence: 99%
“…24 We recently determined that elderly patient experiencing anaphylaxis without concomitant skin symptoms tended to have more severe reactions. 25 Our findings are in concordance with those of a recent retrospective study from Fehr et al, 22 who identified lack of skin symptoms as a risk factor for severe VIA.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies also observed this phenomenon. 21,22 Subsequently, the correlation of BST levels with the severity of anaphylaxis led us to identify an interaction between the absence of skin symptoms and VIA by using generalized linear regression.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for severe systemic sting reactions in wasp ( Vespula spp.) and honeybee ( Apis mellifera ) venom were examined in 480 allergic patients [ 89 ]. The clinical history is essential for the allergological workup and therapeutic decision on Hymenoptera venom allergies.…”
Section: Anaphylaxis Drug Reactionsmentioning
confidence: 99%